Ketogenic Diet Complications - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Serious adverse events are reported in five (10%) of 52 children, aged 1.5-16 years, treated with the ketogenic diet (4:1 ratio/fat: carbohydrate) over a 22-month period at the Montefiore Medical Center and Albert Einstein College of Medicine, Bronx, NY.